CAPACITY BUILDING OF HEALTH CADRES IN PREVENTING STUNTING IN DISASTER-PRONE AREAS (CASE IN SIDOMULYO VILLAGE, LUMAJANG REGENCY) - Husnul Khotimah; Widya Rahmawati; Mustika Dewi; Samichah Samichah; Diyah Ayu Puspitasari (Caring : Jurnal Pengabdian Masyarakat, 2023)
Stunting is a child development disorder characterized by a lack of optimal height due to malnutrition or recurrent infections. Stunting can have short and long-term impacts, including the disturbance of health problems, intelligence, risk of chronic disease, and decreased productivity. The purpose of the project: 1) Explore the problem of stunting, its causes and efforts to improve it in the activity area; 2) Increase the knowledge and skills of cadres related to early detection and management of stunting by cadres, maternal and child health, the practice of making MP-ASI B2SA, 3) Improve the completeness of POSYANDU’s equipment, and 4) Increase motivation, self-confidence, and cooperation of cadres. This activity involved 38 cadres from 7 POSYANDU and one regional midwife. The results of the FGD found cadres' understanding of stunting, 8 factors that cause it, and 5 efforts to prevent and overcome it. The results of the cadre training showed a significant increase in cadre knowledge scores of stunting prevention. The result of the practice of making MP-ASI B2SA is the cadres can make menus with attractive appearance and good taste. Fulfilment of Posyandu completeness, motivation, self-confidence, and cadre cooperation has been carried out, hope that in the future they can carry out their duties better. It can be concluded that the role of POSYANDU cadres plays an important role in preventing stunting in Sidomulyo Village, Pronojiwo Subdistrict, Lumajang Regency.